2020
DOI: 10.1186/s41983-020-00244-6
|View full text |Cite
|
Sign up to set email alerts
|

A brief review of the neurological manifestations of the coronavirus disease

Abstract: Introduction It has been demonstrated experimentally that the coronavirus can enter the central nervous system through olfactory nerves and can even reach medulla. Neurological manifestations are observed more frequently in patients with coronavirus disease. Main text The aim of the review is to seek evidence for infection of the nervous system by the human coronavirus and study the neurological manifestations of the coronavirus and its treatment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 47 publications
0
2
0
2
Order By: Relevance
“…Notably, we found that the most common form of encephalitis in COVID‐19 is autoimmune encephalitis [9,21,24,30,33]. There have also been reports of acute haemorrhagic necrotising encephalopathy [48] and Guillain–Barré syndrome [49] which are known to develop via molecular mimicry, further supporting the theory of molecular mimicry as the pathophysiology of encephalitis as a complication of COVID‐19. Overall, primary data from COVID‐19 patients with encephalitis remains limited, hence conclusions regarding the mechanistic properties and pathophysiology of encephalitis in COVID‐19 cannot be drawn at present.…”
Section: Discussionmentioning
confidence: 55%
“…Notably, we found that the most common form of encephalitis in COVID‐19 is autoimmune encephalitis [9,21,24,30,33]. There have also been reports of acute haemorrhagic necrotising encephalopathy [48] and Guillain–Barré syndrome [49] which are known to develop via molecular mimicry, further supporting the theory of molecular mimicry as the pathophysiology of encephalitis as a complication of COVID‐19. Overall, primary data from COVID‐19 patients with encephalitis remains limited, hence conclusions regarding the mechanistic properties and pathophysiology of encephalitis in COVID‐19 cannot be drawn at present.…”
Section: Discussionmentioning
confidence: 55%
“…Iste promjene s hipometabolizmom moždanog debla i talamusa su uočene u fazi nakon COVID-19 kod bolesnika s kognitivnim smetnjama trajanja dužeg od 3 tjedna. U sljedećoj studiji (8 bolesnika u subakutnoj i kroničnoj post-COVID-19 fazi) uočene su slične promjene na PET-FDG obostrano fronto-parijetalno koje su se povukle nakon 6 Bol u mišićima i mišićna slabost se često javljaju kod hospitaliziranih, ali i kod ambulantnih bolesnika s COVID-19, a učestalost pojavljivanja varira u pojedinim izvještajima i kreće se od 20-50% [9,60] . Poznato je da i druge virusne bolesti kao što je npr.…”
Section: Cerebrovaskularni Incidentiunclassified
“…poremećajima te vaskularnim oštećenjima koji rezultiraju neurološkom bolešću [8] . Imunološki odgovori domaćina pokrenuti za vrijeme ili nakon virusnih infekcija također mogu rezultirati autoimunim oštećenjem živčanog tkiva što je slučaj u primjerima Guillain Barré-ovog sindroma (GBS), akutnog diseminiranog encefalomijelitisa (ADEM) ili akutnog transverzalnog mijelitisa (ATM) [9] .…”
unclassified
“…[17][18][19][20] To confirm the above notion reports from various hospitals show that many patients of COVID-19 suffered from encephalitis, anosmia, acute cerebrovascular disease, and Guillain-Barre syndrome (GBS). [21][22][23][24] This implies that SARS-CoV-2 can cause numerous complications in the brain. Therefore, this review aims at examining all the possibilities of the virus entering the CNS, interacting with neurons and glia, causing neuroinflammation and the neurodegenerative disorders connected with COVID-19.…”
Section: Introductionmentioning
confidence: 99%